The Influence of Service Quality on Customer Satisfaction (A Study on J&T Express in the Rumah Tiga Village Community) - Lefteuw, Rosalina; Rehatta, Geradin; Wairisal, Paulus Liberthy (Universitas Pattimura, 2024)
This study aims to investigate the influence of service quality on consumer satisfaction, particularly in the context of services provided by J&T Express. The research employs a quantitative approach and survey method, collecting data through questionnaires distributed to consumers who use J&T Express delivery services. The service quality variables evaluated include tangibles, reliability, responsiveness, assurance, and empathy, while consumer satisfaction encompasses expectation alignment, repurchase intention, and willingness to recommend. The population for this study consists of the residents of Rumah Tiga village, with samples selected through purposive sampling. The results of this study indicate that the service quality of J&T Express significantly impacts consumer satisfaction. Aspects such as tangibles, reliability, responsiveness, assurance, and empathy positively contribute to consumer satisfaction, including expectation alignment, repurchase intention, and willingness to recommend.